2020
DOI: 10.21203/rs.3.rs-51343/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilization of Electronic Medical Record and Associated Factors Among Health Professionals in Public Health Facilities With Service Delivery, Eastern Ethiopia

Abstract: Backgroundadoption of electronic medical record (EMR) systems in the healthcare delivery has the potential to transform healthcare in terms of saving costs, reducing medical errors, and data quality. However, even if a lots of efforts in the use of electronic health records, such systems have not been implemented and used at expected scale. Thus, his study assessed utilization of electronic medical record and associated factors among health professionals in Eastern Ethiopia.Methodsan institutional based analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…Despite differences among study participants, experience and availability of computerized EMR training were significantly associated. Health professionals who had trained in EMR systems were more likely to be willing to use the EMR system as compared to those who had not trained in any EMR systems before, and this is in line with other findings [ 8 , 18 , 20 – 22 ], which are explained by the evidence that training and education usually change people’s views, willingness, knowledge, and skills on EMR systems [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite differences among study participants, experience and availability of computerized EMR training were significantly associated. Health professionals who had trained in EMR systems were more likely to be willing to use the EMR system as compared to those who had not trained in any EMR systems before, and this is in line with other findings [ 8 , 18 , 20 – 22 ], which are explained by the evidence that training and education usually change people’s views, willingness, knowledge, and skills on EMR systems [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…This may be because health professionals with good knowledge tend to accept the advantages of technology and are more likely to be willing to use the EMR system. As discussed in other studies [ 8 , 18 , 19 ], health professionals who have good knowledge of the EMR system are more likely to be willing to use the EMR system than their counterparts or those who have poor knowledge of the EMR system. This is also a good explanation for the need to create awareness and strengthen continuous capacity building among less knowledgeable health professionals to narrow the knowledge gaps found about the EMR systems so that they will have a good willingness to use EMR and develop their knowledge for better use of the EMR system.…”
Section: Discussionmentioning
confidence: 91%
“…This could be explained by the fact that professionals could likely be willing to use the system if they have a favorable and positive image with good interest towards the system. Previous studies had also shown that health professional’s attitude affects not only their readiness but also the actual utilization of the system [ 22 ]. The finding is also supported by qualitative study results.…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, studies had been carried out on knowledge, attitude, willingness, and acceptance of electronic records [18,25,[55][56][57][58][59][60][61][62]. To the best of the researcher's knowledge, very few studies were conducted on the readiness of electronic medical records (EMRs) at purposively selected primary health facilities in northwest Ethiopia which showed the level of readiness was 54.1% [63] and 62.3% [64].…”
Section: Introductionmentioning
confidence: 99%